Education and Skill Development: A Pathway to Sustainable Growth (International Journal of Scientific Research and Management (IJSRM), 2025)
Education and skill development are fundamental to individual and societal progress, shaping the workforce and driving economic growth. This paper explores the interconnection between education systems and skill acquisition, emphasizing the role of formal and informal learning in developing a competent workforce. Education serves as the foundation for cognitive and analytical abilities, while skill development ensures practical application and adaptability to evolving job markets. Technological advancements and globalization have heightened the need for continuous learning, making lifelong education a necessity. This study also examines the role of vocational training, technical education, and digital learning platforms in enhancing workforce capabilities. Challenges such as the skill gap, lack of access to quality education, and disparities in educational opportunities across different socio-economic groups are discussed. The paper concludes with policy recommendations for integrating skill development with traditional education to meet the demands of the 21st-century job market. By fostering a synergy between education and skill enhancement, societies can achieve sustainable development and economic resilience.